Peran Price Discount Dalam Memoderasi Pengaruh Social Media Marketing dan Product Knowledge Terhadap Purchase Intention Produk Visval Bags - Ulmaghfiroh, Nisa; Woelandari, Dewi Sri; Vikaliana, Resista; Setyawati, Novita Wahyu (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2021)
The purpose of this study was to determine the effect of social media marketing and product knowledge on the purchase intention of Visvalbags products with a price discount as a moderating variable. This study uses a quantitative approach using a sample of 152 respondents, namely the millennial generation who live in North Bekasi using accidental sampling technique. The data analysis technique used is the classic assumption test, multiple linear regression test, hypothesis testing, and determination coefficient test using the SPSS version 21 tool. The results show that social media marketing and product knowledge variables have a significant positive effect on purchase intention, but the variables Price discount cannot moderate the relationship between social media marketing and product knowledge on the purchase intention of Visval Bags products for the millennial generation in North Bekasi.